PEMBENTUKAN LINGKUNGAN PEMBELAJARAN BAHASA ARAB DI SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH (STITAF) SIMAN LAMONGAN - Muhammad Afifuddin (CENDEKIA, 2021)
This study aims to determine the formation of an environment in supporting Arabic language learning at STITAF. It can be said that an environment that supports learning Arabic can improve the quality of language learning itself. One of the main strategies in strengthening Arabic that can be applied is to build a supportive learning environment by facilitating the language learning process to be more interesting and optimal. This research was conducted with a qualitative approach, data obtained from a series of observations, interviews, and documentation in the STITAF environment. The results of this study illustrate that there is a serious effort from the Tarbiyah Al-Fattah College of Sciences (STITAF) in Lamongan to strengthen Arabic language learning in the form of the Center for Language Development and Islamic Education (PPBK) for teaching Arabic with four Arabic language skills: istimak, kalam, qiraah and kitabah, which according to the author's view are quite successful in increasing students' interest in studying and mastering Arabic in a comprehensive manner. This study describes two aspects of strengthening and mastery of Arabic with language development programs and aspects of pesantrenan to animate the intellectuals of the STITAF academic community in the pedagogic, affective and psycho-motor domains. The PPBK institution is the driving force for achieving comprehensive mastery of Arabic in the STITAF environment in particular and other units under the auspices of the Al-Fattah Siman Lamongan Islamic Boarding School Foundation and for the general public.